Pelatihan Pembuatan Website Desa Wisata Di Desa Wisata Meler, Kabupaten Manggarai, NTT - Sebastianus Menggo; Yosefina Rosdiana Su; Rizki Adiputra Taopan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Natural charm, cultural attractions and agro-tourism are the main objects of Meler tourism village. These tourism objects not only provide a wonderful natural persona (rice field spider web terrace) but also a variety of traditional dances that contain historical, educational and humanistic values that are universally applicable. These advantages can be utilized to boost the economy of rural communities. However, tourism village administrators must be digitally literate in order to maximize the economic impact of these tourism assets. The outcome target of this community service is to improve the digital literacy skills of the seven Meler tourist village administrators. This community service was carried out at the Meler village office for two months (May – June 2021), twice a week. A number of methods have been applied to meet the intended outcome targets, namely lecturing, questions and answers, discussions, demonstrations and presentations. The results indicate that the training participants have understood and applied the concept of digital literacy in managing tourism villages.